Representation Of Liberal Feminism In Greta Gerwig's Little Women Movie - Salam, Amanda Riskia; Rullyanti, Merry; Sembiring, Lina Tri Astuty (Literary Criticism, 2025)
Abstract This study aims to analyze the portrayal of liberal feminism in Greta Gerwig's film "Little Women" This study employs a descriptive qualitative approach. This method aims to elucidate the formation of the Representation of Liberal Feminism by analyzing each scene and speech in the movie "Little Women". This research focuses on the film "Little Women" directed by Greta Gerwig in 2019. The research use an observation checklist as the primary tool. This study observation checklist is derived from Stuart Hall's theory (1997), which categorizes Representation into three distinct components: Intentional, Construction, and Reflective. The writer also found moral values based on the theory of Kinnier (2000) which combines moral values into six categories. The results showed that there were seven results of the types of representation shown in the movie " Little Women". Each of these categories, the one that reflects liberal feminism the most is intentional representation. Another finding is the moral values, the most common moral values is a commitment to something greater than oneself. Keyword: Representation ofLiberal Feminism, Little Women Movie